PENGELOLAAN ASET DAERAH BERBENTUK BANGUNAN DI KOTA PARIAMAN DALAM RANGKA TERTIB ADMINISTRASI - Fauzan Zakir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this paper is to examine the management of building assets in the City of Pariaman in the context of administration. The research used is naormative juridical. The implementation of the work on the management of regional goods which is charged is not optimal, as well as inadequate funding to carry out the management of regional property, so that activities to support the orderly implementation of the management of regional goods do not run effectively as well as funding for procurement of goods which must be in accordance with the facilities and infrastructure which should be used to cover work desks, work chairs, etc., does not yet meet the standards for facilities and infrastructure determined by the City of Pariaman Regulations. There must be firmness and clarity carried out by DPPKA in reporting goods to each SKPD so that reporting of the use of goods is timely